Predicting The Reliability Of A Repairable System With Competing Failure Modes - Wong , Wai Kit (2009)

(untitled)
The main objective of this project is to analyze the failure data of centrifugal pumps that were provided by a petrochemical plant and to develop a reliability model to predict the failure occurrences for each failure modes.